Bank Loan Loss Provisions Behaviour: An Empirical Analysis of Indian banking industry. - LI, TONG (2016)
This paper aims to test the determinants of loan loss provisions in Indian banking system over the sample period 2009-2014 with respect to sample bank’s efficiency performance level. We test the hypothesis of income smoothing, capital management and the business cycle, and examine whether the x-efficiency and other control variables influences loan loss provisions behaviour. In the first stage, these efficiency scores are estimated by the Stochastic Frontier Approach. And in the second stage, the Generalized Method of Moments estimator is applied in the analysis. The results of this paper are not consistent to the hypothesis of income smoothing and capital management. Indian banks do not exhibit pro or counter-cyclical provisions and x-efficiency hypothesis in this model.